Early Life Stress Induced DNA Methylation of Monoamine Oxidases Leads to Depressive-Like Behavior - Xu, Qiuyue; Jiang, Mingchen; Gu, Simeng; Wang, Fushun; Yuan, Bin (Frontiers in Cell and Developmental Biology, 2020)
Major depressive disorder (MDD) is coming to be the regarded as one of the leading causes for human disabilities. Due to its complicated pathological process, the etiology is still unclear and the treatment is still targeting at the monoamine neurotransmitters. Early life stress has been known as a major cause for MDD, but how early life stress affects adult monoaminergic activity is not clear either. Recently, DNA methylation is considered to be the key mechanism of epigenetics and might play a role in early life stress induced mental illness. DNA methylation is an enzymatic covalent modification of DNA, has been one of the main epigenetic mechanisms investigated. The metabolic enzyme for the monoamine neurotransmitters, monoamine oxidases A/B (MAO A/MAO B) are the prime candidates for the investigation into the role of DNA methylation in mental disorders. In this review, we will review recent advances about the structure and physiological function of monoamine oxidases (MAO), brief narrative other factors include stress induced changes, early life stress, perinatal depression (PD) relationship with other epigenetic changes, such as DNA methylation, microRNA (miRNA). This review will shed light on the epigenetic changes involved in MDD, which may provide potential targets for future therapeutics in depression pathogenesis.